Digital Inaccessibility of Women Entrepreneurs in Marginal Communities of Guayaquil- Ecuador - Vásquez-Luna , Luz-Elvira (2023)
Female entrepreneurship in marginal communities presents many obstacles to its growth, one of them is the digital divide due to lack of internet access and digital illiteracy. This study presents the testimony of a group of women entrepreneurs from a marginal community in Guayaquil - Ecuador, who start businesses to cover their basic needs. The methodology used was mixed, qualitative through the use of structured and in-depth interviews using the NVivo software, and quantitative trough a survey applying logistic regression in SPSS. The findings of this study demonstrate the digital illiteracy of women entrepreneurs from marginal communities, who require technological training to avoid difficulties when surfing the net, even more so in the current times when, due to the pandemic, most businesses apply digital strategies to stay in the market.